2016
DOI: 10.1042/bsr20160290
|View full text |Cite|
|
Sign up to set email alerts
|

Modulation of miR-146a/complement factor H-mediated inflammatory responses in a rat model of temporal lobe epilepsy

Abstract: Increasing evidence supports the involvement of inflammatory and immune processes in temporal lobe epilepsy (TLE). miRNAs represent small regulatory RNA molecules that have been shown to act as negative regulators of gene expression controlling different biological processes, including immune system homoeostasis and function. We investigated the expression and cellular distribution of miRNA-146a (miR-146a) in a rat model of TLE. Prominent up-regulation of miR-146a activation was evident in 1 week after status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 63 publications
0
48
0
Order By: Relevance
“…On the other hand, a pro-inflammatory profile has also been reported. He et al demonstrated that miR-146a inhibition decreased seizure susceptibility in animal models [25]. It is yet to be completely understood if miR-146a acts as neuroprotective/antiinflammatory or neurodamaging/pro-inflammatory factor in epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a pro-inflammatory profile has also been reported. He et al demonstrated that miR-146a inhibition decreased seizure susceptibility in animal models [25]. It is yet to be completely understood if miR-146a acts as neuroprotective/antiinflammatory or neurodamaging/pro-inflammatory factor in epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a new wave of biomarker research has emerged, focusing on epigenetic markers, with micro-RNAs (miRNAs) assuming a prominent role. MiR-NAs are small non-coding RNA molecules (19)(20)(21)(22)(23)(24)(25) nucleotides in length) that function as post-transcriptional regulators of gene expression [8].…”
Section: Introductionmentioning
confidence: 99%
“…The enduring seizure‐suppressing effect of transient miR‐146a supplementation in early stages of epilepsy suggests an epileptogenesis‐inhibiting and thus disease‐modulating effect of miR‐146a. In contrast, He et al reported that the opposite strategy, i.e., miR‐146a inhibition with a single intracerebroventricular injection of a miR‐146a antagomir, reduced seizure frequency in a rat model of TLE (He et al, ). This apparent controversy, which may be due to different timing, different epilepsy models or potential off‐target effects, requires further detailed analysis of the function of this microRNA in seizure regulation and epileptogenesis.…”
Section: Candidate Micrornas With Therapeutic Potential In Epilepsy Amentioning
confidence: 98%
“…MiR‐146a is of particular interest for epilepsy etiology because it is highly expressed in astrocytes and regulates neuroinflammation (Li et al, ; Iyer et al, ; Kong et al, ), a process believed to be involved in epileptogenesis (Vezzani et al, ). Indeed, miR‐146a expression was shown to be the highest during epileptogenesis, i.e., in the latent and chronic stages in rat models of TLE (Aronica et al, ; Hu et al, ; Omran et al, ; He et al, ). Omran et al () also found up‐regulated levels of miR‐146a in children with mesial TLE (mTLE) confirming earlier work in human TLE (Aronica et al, ).…”
Section: Candidate Micrornas With Therapeutic Potential In Epilepsy Amentioning
confidence: 99%
See 1 more Smart Citation